2021
DOI: 10.1111/all.15030
|View full text |Cite
|
Sign up to set email alerts
|

EAACI Biologicals Guidelines—Omalizumab for the treatment of chronic spontaneous urticaria in adults and in the paediatric population 12–17 years old

Abstract: Chronic spontaneous urticaria (CSU) imposes a significant burden on patients, families and healthcare systems. Management is difficult, due to disease heterogeneity and insufficient efficacy of classical drugs such as H 1 R-antihistamines. Better understanding of the mechanisms has enabled a stratified approach to the management of CSU, supporting the use of targeted treatment with omalizumab. However, many practical issues including selection of responders, the definition of response, strategies to enhance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 116 publications
(218 reference statements)
0
23
0
Order By: Relevance
“…The UAS7 score is self-reported by the patient and is the gold standard for classifying patients as complete responders, partial responders, or non-responders [ 2 ]. UAS7 measures scores daily for seven consecutive days with two versions: once-daily documentation and the UAS7 TD with twice-daily documentation [ 32 ]. Both scores have high sensitivity to change and may be used to determine clinical response to treatment [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The UAS7 score is self-reported by the patient and is the gold standard for classifying patients as complete responders, partial responders, or non-responders [ 2 ]. UAS7 measures scores daily for seven consecutive days with two versions: once-daily documentation and the UAS7 TD with twice-daily documentation [ 32 ]. Both scores have high sensitivity to change and may be used to determine clinical response to treatment [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The management of urticaria has progressed substantially over the past two decades, with disease control possible for at least two-thirds of patients [144][145][146] . Increased understanding of disease pathogenesis underpins an expanding pipeline of targeted therapies with improved adverse effect profiles compared with traditional immunosuppressants (Table 3).…”
Section: Managementmentioning
confidence: 99%
“…Lowered FcεRI expression may render the cells less susceptible to activation by IgE and IgG anti-FcεRI and prevent histamine release and inflammation 167 . As the step-up treatment from antihistamines, omalizumab, as an add-on therapy, has the strongest evidence base and recommendations of all possible treatments for CSU in patients ≥12 years of age 146 . A meta-analysis of 67 real-life CSU studies reported complete and partial response rates of 72% and 18%, respectively, comparable with efficacy in clinical trials, with a mean adverse effect rate of 4% 168 .…”
Section: Omalizumabmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Different biologicals targeting IgE have been developed and assayed as therapeutic strategies for such diseases. 5 Up to date, omalizumab, an IgG1 humanized monoclonal antibody (mAb) that binds free IgE with an affinity of 6.8 nM, is the only one approved for allergic asthma, 6 chronic spontaneous urticaria (CSU) [7][8][9] and chronic rhinosinusitis with nasal polyps (CRSwNP). 10 Omalizumab is a safe and effective treatment for many patients, but several limitations associated with its moderate affinity for IgE and its specific mode of action have been linked to the lack of efficacy reported for some patients and specific disease conditions.…”
Section: Introductionmentioning
confidence: 99%